2020
DOI: 10.48550/arxiv.2007.09043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of time-varying kernel densities and chronology of the impact of COVID-19 on financial markets

Abstract: The time-varying kernel density estimation relies on two free parameters: the bandwidth and the discount factor. We propose to select these parameters so as to minimize a criterion consistent with the traditional requirements of the validation of a probability density forecast. These requirements are both the uniformity and the independence of the so-called probability integral transforms, which are the forecast time-varying cumulated distributions applied to the observations. We thus build a new numerical cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The COVID-19 affected the world in different ways, which were studied, analyzed reported rigorously, with some of the studies showing the impact of COVID-19 on financial markets. For example, Garcin et al (2020) reported that COVID-19 had shown a limited impact on Chinese market, whereas the strongest impact was observed on US markets, at the same time that slowest recovery was observed for European markets when compared to Chinese and Korean ones. Topcu and Gulal (2020) and Ashraf (2020) using pooled panel OLS regression method added that the impact of COVID-19 on emerging markets gradually fell and ended by the end of April 2020 with the impact of the outbreak observed highest in Asian emerging markets and lower in European markets.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 affected the world in different ways, which were studied, analyzed reported rigorously, with some of the studies showing the impact of COVID-19 on financial markets. For example, Garcin et al (2020) reported that COVID-19 had shown a limited impact on Chinese market, whereas the strongest impact was observed on US markets, at the same time that slowest recovery was observed for European markets when compared to Chinese and Korean ones. Topcu and Gulal (2020) and Ashraf (2020) using pooled panel OLS regression method added that the impact of COVID-19 on emerging markets gradually fell and ended by the end of April 2020 with the impact of the outbreak observed highest in Asian emerging markets and lower in European markets.…”
Section: Introductionmentioning
confidence: 99%
“…Equation ( 12) reflects temporal structure of the time series as a function of moments 𝑞, i.e., it represents the scaling dependence of small fluctuations for negative values of and large fluctuations for positives values. If (12) represents linear dependence of 𝑞, the time series is said to be monofractal. Otherwise, if (12) has a nonlinear dependence on 𝑞, then the series is multifractal.…”
Section: Multifractal Detrended Fluctuation Analysis (Mf-dfa)mentioning
confidence: 99%
“…If (12) represents linear dependence of 𝑞, the time series is said to be monofractal. Otherwise, if (12) has a nonlinear dependence on 𝑞, then the series is multifractal. (vi) The different scalings are better described by the singularity spectrum 𝑓 (𝛼) which can be defined as:…”
Section: Multifractal Detrended Fluctuation Analysis (Mf-dfa)mentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, financial markets became risky (Ali et al 2020;Barro et al 2020), with a drastic decline in the stock market indices (Czech et al 2020;McKibbin and Vines 2020) and causing enormous losses (Zhang et al 2020). This pandemic had larger impacts on the US stock market than other regions (Garcin et al 2020). In comparison, Topcu and Gulal (2020) reported a larger impact on Asian stock markets than on European ones.…”
Section: Introductionmentioning
confidence: 99%